THE APPLICATION OF MOBILE APPLICATIONS AND MICROLEARNING SYSTEMS FOR THE EFFECTIVE ACQUISITION OF COMPLEX TECHNICAL TERMINOLOGY IN ENGLISH FOR SPECIFIC PURPOSES (ESP) CLASSES (Eureka Journal of Language, Culture & Social Change, 2026)
This article gives the efficacy of integrating microlearning systems and mobile applications into the process of vocabulary acquisition for engineering students within English for Specific Purposes (ESP) courses. Under conditions of cognitive overload, traditional methods of vocabulary memorization increasingly yield to flexible, chunked instructional technologies. The authors conducted a pedagogical experiment designed to measure the rate and retention of complex engineering and IT terminology acquisition utilizing mobile tracking data. The findings demonstrate that gamified microlearning enhances the productivity of vocabulary memorization by 42% and significantly improves long-term information retention.
Keywords: Microlearning, mobile learning, technical terminology, English for Specific Purposes (ESP), spaced repetition, gamification, cognitive load.